(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
On the past October 24th, 2011, the Pontifical Council for Justice and Peace published a document under the title: “Towards Reforming the International Financial and Monetary Systems in the Context of Global Public Authority”. The paper intended to develop the intuitions presented by Benedict XVI in his encyclical Caritas in Veritate, applying them to the reform of the global financial system. In this article we shall atempt to study some We shall present its contents as much as imprescindible, and we shall focus on their connection with some related intellectual traditions.